Design of a spatial compliant translational joint. (January 2017) - Yang, Tai-Shen; Shih, Po-Jen; Lee, Jyh-Jone
Abstract: This paper presents the design of a novel compliant translational joint with large stiffness ratio and small axis drift. The characteristics of compliant translational joints based on a leaf-spring type joint are investigated. Several types of constructions are analyzed. A novel three-dimensional compliant translational joint is proposed and a design analysis is conducted based on the parametric models. Subsequently, a design optimization is employed with the aid of finite element method. Then, a prototype of the optimized design is fabricated by 3D printing, and tests of specified properties are conducted. Comparisons of the experimental results and simulation results show that this new joint satisfies the design requirements. Highlights: Conceptual design of the spatial compliant translational joint. Characteristics analysis of flexure mechanisms in series, parallel and hybrid connections. Optimization design of a spatial compliant translational joint. FEA simulation and experiment of the optimized spatial compliant translational joint.